Perspective of Death and war in Rupert Brooke’s poem “The Soldier” and Randall Jarrell’s poem “The Death of the Ball Turret Gunner” - Safaa Haqi Ismaiel (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
The current paper attempted to convey the complex selves of the well-known war poets Rupert Brook and Randall Jarrell during and after World Wars I and II. Randall Jarrell was able to express the bitter reality of the war because he participated in the World War II. He witnessed the horror and the destruction which included the deaths of his fellow soldiers, as a result he wrote poems that was brutal and full of ferocious imagery. In his poems, Jarrell presents the horrors of war focusing on the idea of death in it. According to Rupert Brooke, going to war is a noble endeavor and a chance to demonstrate one's patriotism and strength of character. With the outbreak of the World War I Brook was deeply patriotic encouraging the young men to join in what he considered to be a noble fight. Thus he focused on the idea of death and patriotism. The soldiers that Brooke depicts are patriotic to their country; they are ready to sacrifice their life in order to defend their homelands.